(untitled) (Journal of Hama University, 2019)
The purpose of the research is to study the possibility of pathological changes in the histological structure of the parotid gland after exposure to microwave radiation emitted from mobile phone by studying the expression of Ki67 and VEGF. the sample consisted of 16 rabbits divided equally according to exposure to microwave – radiation into two groups: control and experimental, where the experimental group was exposed to the mobile phone one hour daily – 6 days a week – for 6 months. After the end of the exposure period, rabbits were sacrificed and parotidectomy was realized, and thus we obtained 16 tissue biopsies immunohistochemically stained with the monoclonal antibody Ki67 and monoclonal antibody VEGF, and the method of counting positive cells was used in each field of tissue and then calculated the percentage of them from the total cells of the field studied at high magnification 400×.All samples were positive for stained Ki67 and VEGF with increase in expression in the study group, i.e. increased proliferation activity in the glandular tissue and increased in vascular development respectively in the parotid glands as a reaction to the damage caused by exposure to the mobile phone.